Characterization and catalytic properties of MnO₂-modified kaolinite for formic acid oxidation - Asma Shafiq Shathi; Hayatullah; Md. Mominul Islam; Md. Abu Bin Hasan Susan; Muhammed Shah Miran; Md. Golam Mostafa (Sustainable Chemistry for Climate Action)
This study investigates the characterization, and catalytic performance of kaolinite-supported MnO₂ catalysts for formic acid oxidation, aiming to develop sustainable materials for catalytic applications. The composite was synthesized by incorporating MnO₂ into acid-treated kaolinite, and its structural, thermal, and surface properties were analyzed using advanced techniques, including FT-IR, TGA/DTA, UV-Vis, N₂ adsorption-desorption, and BET analysis. FT-IR results showed structural and compositional changes in clay minerals due to acid treatment, calcination, and MnO₂ incorporation, particularly in Si-O-Si, Si-O-Al, and Al-OH functional groups. TGA/DTA analysis revealed alterations in thermal stability and phase transitions with MnO₂ inclusion, indicating enhanced dehydroxylation and water retention properties. UV-Vis absorption spectra confirmed successful MnO₂ nanoparticle synthesis, with a peak at 366 nm consistent with nanostructured MnO₂. N₂ adsorption and BET analysis demonstrated a decrease in surface area and pore volume of acid-treated clay post-calcination, while MnO₂ incorporation improved porosity, particularly at lower concentrations. The clay/0.45 % MnO₂ composite showed optimal catalytic performance for formic acid oxidation, balancing surface area and porosity for enhanced activity. The BJH analysis method (Barrett-Joyner-Halenda)further revealed that higher MnO₂ content increased pore volume and surface area, promoting catalytic and adsorption properties. This study emphasizes the influence of MnO₂ on the morphology, structure, and catalytic properties of kaolinite composites. Future work will focus on optimizing MnO₂ loading and investigating long-term catalytic stability for practical applications in environmental and energy-related fields.